(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article analyzes the pedagogical and psychological mechanisms of the process of formation and development of creative abilities in preschool children and the conditions created in preschool education. The factors influencing the development of creative abilities, the importance of types of activities, as well as the role of the creative approach of the educator and the pedagogical environment are revealed.